Novel DCX pathogenic variant in a girl with subcortical band heterotopia - Papuc Sorina Mihaela; Budisteanu Magdalena; Erbescu Alina; Ionescu Virgil; Iliescu Catrinel; Sandu Carmen; Arghir Aurora (Romanian Journal of Laboratory Medicine, 2022)
Subcortical band heterotopia (SBH), is a brain malformation defined by symmetrical and bilateral heterotopic gray matter bands localized deep within the white matter, between the cortex and lateral ventricles. SBH is the result of abnormal neuronal migration, with improper positioning of the cortical neurons. DCX gene (doublecortin), a microtubule-associated protein with essential roles in neuronal migration and differentiation during brain development, is one of the main contributors to the X-linked Lissencephaly spectrum pathogenesis (OMIM #300067). DCX variants are responsible for SBH in females and isolated lissencephaly in males. Herein, we present a 7-year-old girl with a de novo frameshift variant in DCX gene, unreported by date. The patient has focal complex seizures with onset at 23 months of age, fully controlled with medication, mild tremor and coordination impairment of fine movements and some learning difficulties, otherwise with normal development. The brain magnetic resonance imaging revealed the presence of thick SBH. Direct sequencing of DCX gene revealed a pathogenic heterozygous cytosine duplication in exon 3; this frameshift variant leads to a premature stop codon in position 164 (p.Gln160Profs*5). The variant type and its predicted consequence at protein level correlates with the severity of radiological findings. The clinical presentation of our patient is, however, milder than expected. Our research expands the mutational spectrum of DCX gene in SBH females and provides a detailed clinical and imagistic description of the patient. This paper highlights the utility of single gene sequencing as a first-tier diagnostic test of patients with gene-specific phenotypic features.